Branding Politik “Gemoy”: Konstruksi Citra Prabowo Subianto–Gibran Rakabuming dalam Pemilihan Presiden 2024 - Moch. Ardyan Aviansyah; Ken Akya Aruna Bintang; Salim Salim (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The study examines the political branding strategy of “Gemoy” in constructing the public image of Prabowo Subianto–Gibran Rakabuming during the 2024 Indonesian Presidential Election. Using a digital ethnography approach, the research explores how political messages, visual symbols, and interactive content were produced, circulated, and interpreted across social media platforms such as TikTok, Instagram, X, and YouTube. The findings reveal that the “Gemoy” branding represents a deliberate transformation of Prabowo’s long-established authoritative and military image into a more approachable, humorous, and human-centered persona. This shift aligns with the cultural preferences of younger voters, particularly Generation Z, who engage with political content through entertainment-oriented and participatory digital practices. Public responses indicate that political branding in the digital era operates through emotional resonance and symbolic closeness rather than purely rational political evaluation. Moreover, the study demonstrates that audiences actively participate in reconstructing political meanings through content replication, commentary, and viral trends. Overall, the “Gemoy” branding illustrates how contemporary political communication integrates popular culture and digital interaction to shape political perception and voter engagement.